CARDIO-ANKLE VASCULAR INDEX (CAVI) AND ARTERIAL STIFFNESS ASSESSMENT AT MEDICAL PREVENTION DEPARTMENTS AND UNITS - R. M. Linchak; R. M. Komkov; O. G. Prishchepa; O. B. Shvabskaya (Кардиоваскулярная терапия и профилактика)
Aim. To study the clinical potential and feasibility of the assessment of cardio-ankle vascular index (CAVI) at medical prevention departments and units.Material and methods. The study included 66 patients (13 men and 53 women; mean age 52,26±11,2 years) with very low to very high total cardiovascular risk (CVR) levels and SCORE index 0–25% (mean SCORE index 3,18±4,34%), who underwent volume sphygmography and automatic CAVI measurement.Results. There was a moderately strong, statistically significant correlation between CAVI and age; CAVI and systolic blood pressure (SBP); and CAVI and SCORE. While higher CAVI values were observed among non-smokers and patients with arterial hypertension, these differences were not statistically significant.Conclusion. As a method for arterial stiffness assessment, CAVI measurement is easy to perform, does not require any special preparation, and can be used at medical prevention departments and units as a part of a more detailed preventive examination. A moderately strong, statistically significant correlation was observed between CAVI and SCORE, as well as between CAVI and such SCORE components as age and SBP. However, further research is needed in order to clarify the possibility of CAVI inclusion in prognostic models.